LO05: Rate of prescription of oral anticoagulation in patients presenting with new onset atrial fibrillation/flutter. (May 2020) - Hatam, E.; Ghate, G.; Columbus, M.; Garvida, C.; Aarsen, K. Van
Abstract : Introduction: Atrial fibrillation (AF) and atrial flutter (AFL) are two common arrhythmias that present to the emergency department (ED) and are a major risk factor for stroke. The 2014 Canadian Cardiovascular Society (CCS) guidelines recommend starting oral anticoagulation (OAC) upon ED discharge for patients with CHADS65 scores of ≥1 to reduce stroke risk. The goal of this study was to identify whether the ED patient population presenting with new onset AF/AFL with CHADS65 ≥ 1 are appropriately initiated on OAC by ED physicians. Methods: This was a retrospective chart review (Jan-Dec 2017) of ED visits at two academic hospitals in Ontario. The year 2017 was chosen to allow for adequate time from the publishing of the CCS guidelines for uptake into clinical practice. Inclusion criteria: patients with a new diagnosis of AF/AFL who are discharged by ED physicians. Exclusion criteria: patients with a history of AF/AFL, already on OAC, admitted to hospital, presenting with arrhythmia other than AF/AFL, and charts without adequate information to calculate CHADS65 score. Charts were reviewed in detail to assess CHADS65 score, ED physician decision to prescribe OAC, referral rates to outpatient clinics and timing of follow up. Results: A total of 1272 charts were reviewed. 1124 were excluded. 148 charts were identified as patients with new onset AF/AFL presenting to the ED who were discharged by ED physicians. 24/148 (16%) were appropriately prescribed OAC. 124/148 (84%) were not prescribed OAC. Of these 40/124 (32%) were CHADS65 0 while the other 84/124 (67%) were CHADS65 ≥ 1 who should have been considered for OAC. Further review determined that 78/84 (92%) were referred to outpatient clinics for the decision regarding OAC with the mean (SD) number of days to follow up being 11(±15). Importantly 1/84 (1.2%) returned prior to their scheduled appointment with a stroke. Only 6/84 (7%) had no follow up arranged. Conclusion: Overall, we found that the rate of OAC prescription by ED physicians for patients being discharged with a new diagnosis of AF/AFL with a CHADS65 score ≥1 was 16%. This is despite the CCS 2014 recommendation of starting OAC for all patients with a CHADS65 score ≥1. It appears that ED physicians are continuing to defer the decision to prescribe OAC to outpatient clinics. Further projects can explore barriers to application of the CCS guidelines and create knowledge translation tools.